Yield stability, ecological plasticity and spike productivity reveal adaptive strategies of winter wheat cultivars under hydrothermal variability - I. V. Havryliuk; H. M. Kovalyshyna; O. S. Makarchuk; D. V. Litvinov; R. S. Zhyla; R. O. Spriazhka; O. S. Havryliuk (Regulatory Mechanisms in Biosystems, 2026)
Climate variability increasingly affects winter wheat production by altering genotype × environment interactions and redu c ing the predictability of cultivar performance. Identifying cultivars that combine high yield, stability, ecological plasticity, and valuable spike productivity traits is therefore essential for sustainable wheat production under unstable hydrothermal conditions. This study evaluated grain yield, yield stability, ecological plasticity, homeostaticity, and main spike structure traits of 35 Ukrai n ian winter soft wheat ( Triticum aestivum L.) cultivars grown in the Right-Bank Forest-Steppe of Ukraine during 2022–2024. Grain yield, coefficient of variation, ecological plasticity coefficient, homeostaticity index, spike rachis length, spike weight, number of spikelets per spike, number of grains per spike, and grain weight per spike were assessed using analysis of variance, correlation analysis, and cluster analysis. The study years differed markedly in hydrothermal conditions, providing a contrasting background for cultivar evaluation. Mean grain yield ranged from 508.4 to 661.7 g/m². The highest productivity was recorded for Tsarivna, Svitanok Myronivskyi, Vodohrai Bilotserkivskyi, Zorepad Bilotserkivska, Kraievyd, MIP Dniprianka, and Kvitka Poliv. Tsarivna and Vodohrai Bilotserkivskyi combined high yield with moderate interannual variability and a balanced ecolog i cal response, indicating broad adaptive value. Kesariia Poliska showed the highest homeostaticity and the lowest yield variability, while Romantyka combined stable yield expression with stable spike structure traits. Grain yield was mainly influenced by year and cultivar × year interaction. Correlation analysis revealed strong positive relationships among spike structure traits, particularly between grain number per spike and grain weight per spike, whereas their associations with mean yield were weaker. Cluster analysis distinguished cultivars with different adaptive strategies. The results demonstrate that winter wheat cultivar value cannot be reliably assessed by mean yield alone.